Реалізація цивільної правосуб'єктності транснаціональними корпораціями - Фединяк, Г.С. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуются вопросы реализации гражданской правосубъектности транснациональными корпорациями. Определяются организационно-правовые формы реализации указанной правосубъектности. Определяются органы, которые реализуют договорную правосубъектность транснациональных корпораций, в том числе с принимающим государством. Акцентировано внимание на правовом институте представительства, который используется корпорациями в их деятельности. The questions about the realization of civil legal personality of transnational corporations are investigated in the article. The organizational legal forms of the realization of the given legal personality are defined here. The bodies are defined that realize the contract legal personality of the transnational corporations including with the host states. The attention is paid to the government legal institute, which is used by the corporations in their activity.